Assessment of Postoperative Complications and Outcomes in Patients Undergoing Laparoscopic Cholecystectomy - Sanjeev Yadav; Ramavath Ramesh; Zeeshan Sheikh; Hemanth Satya Subhash Padala; Chapala Shashank; Jasmine Kalsi; Pritee Rajkumar Pandey (Wolters Kluwer Medknow Publications, 2024)
Introduction: A common surgical technique for gallbladder disorders is laparoscopic cholecystectomy (LC), which has the benefits of less postoperative discomfort and quicker recovery. The purpose of this retrospective research was to assess postoperative outcomes and complications in patients having laparoscopic correction. Methods: In total, 200 patients who had LC at the tertiary care center between 2017 and 2022 were the subjects of a retrospective investigation. We gathered and examined data on preoperative conditions, surgical specifics, postoperative results, and demographics. Results: Notable findings from the study were as follows: (1) The average age of the patients was 47.5 years (±12.3), and there were strong correlations (P < 0.001) between age and problems. (2) Significant correlations were found between many covariates and postoperative outcomes, such as a 10% readmission rate and a mean hospital stay of 3.6 days (±1.2) (P < 0.05). (3) Different relationships were seen between the complications (P values ranging from 0.021 to <0.001), including wound infections (6%) and bile duct injuries (2.5%). Conclusion: To enhance patient care, a thorough assessment and focused treatments are required. This study sheds light on the frequency of postoperative problems and outcomes in patients receiving LC.